An energy evaluation for thermal conversion of thermoplastic waste to refined oil products using pyrolysis reaction process system. (2016) - Gabbar, Hossam A.; Aboughaly, Mohamed; Choudhary, Awais
Thermoplastics are converted to hydrocarbon fuels in a chemical reaction called pyrolysis. The work highlights the energy consumption using Aspen HYSYSV8.8 simulations in each process stage starting with granulation, preheating, pyrolysis reactor and condensation as major process steps concluding that the highest required heat duty which is around 61% in the pyrolysis reactor thus having the highest operating cost. Aspen HYSYS is used to calculate energy consumption in each stage. The design is 10 tonne/hour of thermoplastic mixture. Pyrolys is reactor operating temperatures are 550°C at atmospheric pressure. The condensation system shows recovery duty of 3.4 MW of which can be used to heat cold streams. Pinch analysis was also carried out to design a heat exchanger network (HEN) between hot and cold streams in order to reduce energy consumption. Heat recovery from pyrolysis reactor effluent gases shows possible 3.439 MW recovery in a 10 tonne per hour pyrolysis plant.